2008
DOI: 10.1007/s00787-008-0707-7
|View full text |Cite
|
Sign up to set email alerts
|

Examining relations between psychopathology and psychopathy dimensions among adolescent female and male offenders

Abstract: Aim: This study was performed to investigate relations between psychopathology and psychopathy in adolescent female and male detainees. Method: We examined 91 male and 123 female adolescent detainees (aged 14–19) for psychopathology -using the Youth Self Report, the Overt Aggression Scale-Modified and a Conduct Disorder Self Report Scale- and for psychopathic dimensions using the psychopathy checklist youth version (PCL:YV). Based on a linear regression analysis we compared the specific associations between ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
48
5
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 74 publications
9
48
5
3
Order By: Relevance
“…Thus, evidence suggests that psychopathy may be expressed differently amongst female offenders in comparison to their male counterparts (Forouzan & Cooke, 2005;Hamburger, Lilienfeld, & Hogben, 1996;Nicholls, Ogloff, Brink, & Spidel, 2005;Sevecke, Lehmkuhl, & Krischer, 2009;Vitale, Smith, Brinkley, & Newman, 2002). Finally, investigations to explore gender differences with regards to sexual aggression in psychopathic non-offenders are seemingly non-existent.…”
mentioning
confidence: 99%
“…Thus, evidence suggests that psychopathy may be expressed differently amongst female offenders in comparison to their male counterparts (Forouzan & Cooke, 2005;Hamburger, Lilienfeld, & Hogben, 1996;Nicholls, Ogloff, Brink, & Spidel, 2005;Sevecke, Lehmkuhl, & Krischer, 2009;Vitale, Smith, Brinkley, & Newman, 2002). Finally, investigations to explore gender differences with regards to sexual aggression in psychopathic non-offenders are seemingly non-existent.…”
mentioning
confidence: 99%
“…In line with that, it was found that psychopathy in men compared to women was more associated with antisocial behaviour (Strand & Belfrage, 2005), violence and criminal recidivism (Verona & Vitale, 2006), as well as with impulsivityrelated tendencies (e.g., difficulties resisting urges, sensation seeking) (Miller, Watts, & Jones, 2011). In contrast, psychopathy in women was associated with more fraud in criminal history, manipulative and self-destructive behaviour during therapy (de Vogel & Lancel, 2016), and internalizing symptoms such as depression (Sevecke, Lehmkuhl, & Krischer, 2009). There are also gender differences in values with females reporting lower hedonistic values (Abraham & Rahardjo, 2015).…”
Section: Gender Differences In Psychopathy and Valuesmentioning
confidence: 78%
“…This condition is the result of an imbalance between stimulation and inhibition of different brain zones regarding a specific stimulus. In addition, current difficulties in approaching PD and their subtypes that constitute dimensions together with the differential expression of other comorbid syndromes and about which important clinical, neuropsychological, neurophysiological, biochemical and genetic differences are established (for example, age related with the severity of symptoms, the conduct disorder with or without child abuse and so on) (Evenden, 1999;Morgan & Lilienfeld, 2000;Sevecke, Lehmkuhl, & Krischer, 2008) suggest the necessity to advance in the taxonomy of theses syndromes through the use of several biomarkers that help to discriminate the subtype and establish a differential biological correlate. An exhaustive approximation to the spectrum of PD must include biomarkers that are co-related closely with impulsive subtypes, aggressive subtypes, and neurocognitive features associated with the patterns of int.j.psychol.res.…”
Section: Discussionmentioning
confidence: 99%